Effect of glyphosate management, formulations and rates on the agronomic performance of maize with the cp4epsps gene - Albrecht, Alfredo Junior Paiola (2024)
Second-generation glyphosate-tolerant maize (Roundup Ready 2, RR2) is characterised by the expression of the cp4epsps gene. Despite some studies suggesting possible undesirable effects from the application of glyphosate in RR2 maize, other reports have demonstrated glyphosate selectivity for RR2 plants, with minor damage symptoms, if any, and with no negative effects on the chlorophyll indices. The aim of this study was to evaluate the effect of different types of glyphosate management, formulations and rates of application on chlorophyll indices and the agronomic performance of an RR2 maize genotype expressing the cp4epsps gene. Five experiments were conducted in a full factorial design (2 x 5 x 5) to evaluate two types of management, two formulations and five rates of glyphosate. Damage symptoms, chlorophyll indices and variables related to agronomic performance (plant height, stem diameter, yield and 100-grain weight) were evaluated. Similar crop responses were found for each of the glyphosate formulations (potassium salt and isopropylamine salt) and types of management (single application and sequential application) under test, indicating that the use of glyphosate-based commercial products affords flexibility in terms of formulation and frequency of application. Glyphosate formulated as potassium salt or isopropylamine salt and applied to RR2 maize either in a single application (full rate) or in two sequential applications (each at half rate) has a similar effect and may therefore be used without distinction. However, it is important to consider the rate of application since high rates of glyphosate (especially greater than 1, 440 g ae ha-1) may affect the development and production of RR2 maize.